Differences Between Syariah Money Markets in Indonesia and Kuwait - Safnah Soleha; Hikmah Indri Yani Harahap; Adelia Safitri; Maryam Batubara (Sean Institute, 2025)
This study compares the Islamic money markets in Indonesia and Kuwait, focusing on their characteristics, instruments, and regulations. The Islamic money market, operating without riba (interest), gharar (uncertainty), and maisir (speculation), is a vital short-term financial instrument in the global Islamic financial system. Indonesia, as the country with the largest Muslim population, demonstrates a strong commitment to developing its Islamic money market through various regulations and innovative products such as Sharia Bank Indonesia Certificates (SBIS) and State Sharia Securities (SBSN). On the other hand, Kuwait is a pioneer in Islamic finance in the Middle East, possessing a mature Islamic money market strictly regulated by the Central Bank of Kuwait (CBK). Although both are based on Sharia principles, their implementation varies between countries due to factors such as regulation, market infrastructure, adoption rates, and macroeconomic conditions. This research employs a descriptive qualitative literature review using secondary data. The findings indicate that Indonesia excels in instrument diversification and the development of Islamic money market infrastructure, supported by progressive regulations. However, challenges in Indonesia include low Islamic financial literacy and the need for broader instrument diversification. Meanwhile, Kuwait, despite its strong foundation, faces the challenge of high reliance on Commodity Murabahah as a primary instrument, necessitating more diverse product innovation. This comparison is expected to enrich Islamic finance literature and provide practical implications for the global development of Islamic money markets.